2020
DOI: 10.3390/e22040403
|View full text |Cite
|
Sign up to set email alerts
|

Rate Adaption for Secure HARQ-CC System with Multiple Eavesdroppers

Abstract: In this paper, we studied the secure transmission of a hybrid automatic repeat request with chase combining (HARQ-CC) system, under the existence of multiple eavesdroppers and limited latency. First, we analyzed some critical performance metrics, including connection outage probability (COP), secrecy outage probability (SOP) and effective secrecy throughput (EST). Then, to maximize the EST, three optimization problems of rate adaption were discussed: (i) optimizing the code rate with a given secrecy redundancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The authors in [171] have proposed a suitable performance metric for URLLC networks, i.e., COP that maintains a trade-off between latency, reliability, security and network throughput. In another research work [172], the authors have analysed the performance of PLS in RIS-assisted hybrid automatic repeat request (HARQ) system. The system setup is composed of single antenna transmitter, receiver, Eve and an RIS in non-LoS scenario.…”
Section: Volume 15mentioning
confidence: 99%
“…The authors in [171] have proposed a suitable performance metric for URLLC networks, i.e., COP that maintains a trade-off between latency, reliability, security and network throughput. In another research work [172], the authors have analysed the performance of PLS in RIS-assisted hybrid automatic repeat request (HARQ) system. The system setup is composed of single antenna transmitter, receiver, Eve and an RIS in non-LoS scenario.…”
Section: Volume 15mentioning
confidence: 99%
“…It has been demonstrated that an eavesdropper cannot obtain the same diversity gain as a legitimate user, since re-transmissions rely solely on the latter user [ 31 ]. As another import metric, effective secrecy throughput (EST) with multiple eavesdroppers has been optimized in secure HARQ transmissions [ 32 ]. Additionally, Park proposed Kalman combining-based iterative detection and decoding schemes for multiple-input multiple-output (MIMO) systems with HARQ [ 33 ], and Wu et al achieved a tradeoff between timeliness and reliability for HARQ-CC aided non-orthogonal multiple-access (NOMA) systems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%